Support Vehicles, Components and Modules of the International Space Station - Dowling, Dominick, author 648085; Rico, Colt, author 648086 (Delhi, India : World Technologies, 2012)
Soyuz is a series of spacecraft designed for the Soviet space program by the Korolyov Design Bureau in the 1960s, and still in service today. The Soyuz succeeded the Voskhod spacecraft and was originally built as part of the Soviet Manned Lunar program. The Soyuz spacecraft is launched by the Soyuz rocket, the most frequently used and the most reliable launch vehicle to date. The Soyuz rocket design is based on the Vostok launcher, which in turn was based on the 8K74 or R-7a intercontinental ballistic missile. The first unmanned Soyuz mission was launched November 28, 1966; the first Soyuz mission with a crew (Soyuz 1) was launched April 23, 1967, but the cosmonaut on board, Vladimir Komarov, died during the flight's crash-landing. Soyuz 2 was an unmanned mission, and Soyuz 3, launched on October 26, 1968, was the first successful Soyuz manned mission. The only other fatal mission, Soyuz 11, killed the crew of three also during re-entry due to premature cabin depressurization. Despite these early fatalities, Soyuz is presently widely considered the world's safest, most cost-effective human spaceflight system due to unparalleled length of operational history. The Soyuz spacecraft family is still in service. Soyuz spacecraft were used to carry personnel to and from Salyut and later Mir Soviet space stations, and are now used for transport to and from the International Space Station.